Рассеяние волнового пучка тонким диэлектрическим цилиндром с потерями - Одаренко, Е. Н.; Шматько, А. А.; Свич, В. А. (Weber Co., 2007)
The problem of laser wave beam scattering on the lossy dielectric cylinder is solved. Numerical calculation of scattered field spatial distribution inside and outside the cylinder is carried out and resonant field absorption effect is detected.
Keywords: волновой пучок; диэлектрический цилиндр; рассеяние волны